STUDENTS’ PERCEIVED AREAS OF DIFFICULTIES IN SENIOR SECONDARY MATHEMATICS AND TEACHERS’ VIEWS ON THE CAUSES OF IDENTIFIED DIFFICULTIES IN IKERE LGA, EKITI STATE - OLOFINLAE, Olatona; Jimoh, S.O (IJRDO -JOURNAL OF MATHEMATICS, 2020)
This study examined the perceived difficult topics in secondary school mathematics by students as well as the mathematics teachers’ views of the causes of the identified difficulties in Ikere local Government Area of Ekiti State. This study employed the survey research design. The sample for the study was one hundred (100) SSS 3 students and twenty (20) teachers The study was guided by three (3) research questions and three (3) hypotheses. The instruments used for the collection of data were a 36-item questionnaire tagged “Difficult Concept Identification Questionnaire in Mathematics (DCIQM)” and “Mathematics Difficult Topic Assessment Questionnaire (MDTAQ)”. The instruments were validated and the reliability established using the test-retest method. The data obtained were analyzed using mean with the criterion mean set at 2.5. Also, ANOVA statistic was used to analyze the three (3) hypotheses formulated for the study. The findings of the study revealed that students identified some mathematics topics (longitude and latitude, bearing, mensuration) as difficult. Based on the findings of the study, it was recommended amongst others that workshops should be organized to train mathematics teachers on the effectiveness and efficient strategies that should be adopted for the teaching of the identified difficult mathematics concepts.